Pulmonary Edema in COVID-19 Patients: Mechanisms and Treatment Potential - Cui, Xinyu; Chen, Wuyue; Zhou, Haoyan; Gong, Yuan; Zhu, Bowen; Lv, Xiang; Guo, Hongbo; Duan, Jinao; Zhou, Jing; Marcon, Edyta; Ma, Hongyue (Frontiers in Pharmacology, 2021)
COVID-19 mortality is primarily driven by abnormal alveolar fluid metabolism of the lung, leading to fluid accumulation in the alveolar airspace. This condition is generally referred to as pulmonary edema and is a direct consequence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. There are multiple potential mechanisms leading to pulmonary edema in severe coronavirus disease (COVID-19) patients and understanding of those mechanisms may enable proper management of this condition. Here, we provide a perspective on abnormal lung humoral metabolism of pulmonary edema in COVID-19 patients, review the mechanisms by which pulmonary edema may be induced in COVID-19 patients, and propose putative drug targets that may be of use in treating COVID-19. Among the currently pursued therapeutic strategies against COVID-19, little attention has been paid to abnormal lung humoral metabolism. Perplexingly, successful balance of lung humoral metabolism may lead to the reduction of the number of COVID-19 deaths limiting the possibility of healthcare services with insufficient capacity to provide ventilator-assisted respiration.